Energy and exergy analysis of the condensate pump during internal leakage from the marine steam propulsion system - Poljak, Igor, inženjer brodostrojarstva (Array, 2018)
An energy and exergy analysis of the condensate pump from the marine steam propulsion system during the condensate leakage between pump stages is presented in this paper. Measurements from the steam propulsion system during exploitation were necessary for collecting all the data for the condensate pump analysis. Due to condensate leakage inside the pump casing, the producer specified condensate pressures at the pump outlet could not be obtained during the exploitation. Low condensate pressure at the pump inlet and condensate temperature slightly above the atmospheric significantly influences the pump exergy analysis. Increase in pump load resulted in an increase of pump energy and exergy losses and efficiencies. In the observed load range during the leakage, pump energy losses are between 19.88 kW and 24.78 kW, while pump energy efficiencies are between 11.12 % and 41.54 %. Pump exergy losses are slightly higher, while exergy efficiencies are slightly lower when compared to energy losses and efficiencies. During normal operation, without leakage, the pump energy efficiencies are from 5 % to 20 % higher in comparison with pump operation when the leakage occurs.